Computed tomography–based image-guided brachytherapy for cervical cancer: correlations between dose–volume parameters and clinical outcomes. (23rd November 2017) - Kusada, Takeaki; Toita, Takafumi; Ariga, Takuro; Maemoto, Hitoshi; Hashimoto, Seiji; Shiina, Hideki; Kakinohana, Yasumasa; Heianna, Joichi; Nagai, Yutaka; Kudaka, Wataru; Aoki, Yoichi; Murayama, Sadayuki
Abstract: This study evaluated the oncologic outcomes and complications of cervical cancer patients in terms of CT-based image-guided brachytherapy (IGBT) parameters. Of 68 cervical cancer patients treated with definitive radiotherapy/concurrent chemoradiotherapy, most received whole-pelvis external beam RT (EBRT) of 40 Gy in 20 fractions, pelvic EBRT with central shield of 10 Gy in 5 fractions, and CT-based IGBT of 18 Gy in 3 fractions prescribed to point A. Cumulative EBRT and IGBT doses were calculated as the total equivalent dose in 2 Gy fractions (EQD2). The median follow-up was 31 (3–52) months. The 2-year overall survival, local control, pelvic control, and disease-free survival rates of the 68 patients were 92%, 83%, 82% and 73%, respectively. The HR-CTV D90, length from the tandem axis to left/right margin of the HR-CTV (T-LR), and HR-CTV volume were significant IGBT parameters for predicting local/pelvic control. Patients who received an HR-CTV D90 of >60 Gy, compared with ≤60 Gy, had significantly better local/pelvic control. Furthermore, 70 Gy was a marginally significant HR-CTV D90 cut-off affecting local control. T-LR was an independent IGBT parameter predicting local/pelvic control on multivariate analysis. Three patients developed Grade 3 or higher treatment-related complications. The D2cm 3 of organs at risk were not significant predictors of complications. Future challenges for further improving outcomes include additional interstitial needles for irregularly shaped HR-CTVs, and moderate dose escalation, especially for patients with poor tumor responses.